ASSESSMENT OF IMPORTANT TECHNOLOGICAL PARAMETERS OF NEW MOROCCAN DOMESTICATED TETRAPLOID OAT LINES OF AVENA MAGNA - R. . Manzali; A. . Douaik; M. . Bouksaim; G. . Ladizinsky; N. . Saidi (Труды по прикладной ботанике, генетике и селекции)
Results of studying the oat collection of the N. I. Vavilov All-Russian Institute of Plant Genetic Resources are presented. Field and Nine tetraploid oat lines of Avena magna Murph. et Terr. were assessed for their technological performance. Physicochemical analyses were performed, including moisture, ash, proteins, fibre fractions, lipids, carbohydrates, and minerals. Statistical analysis revealed noteworthy differences in the chemical composition between the cultivars.